Analisis Pengendalian Waktu Pekerjaan Proyek Dengan Menggunakan Metode Fast - Track - Julistyana Tistogondo; Saiful Anwar; Dyah ayu Restuti Wulandari (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2023)
Abstract Due to poor administrative supervision and a lack of collaboration amongst all interested parties, the Situbondo Paramaan Bridge Replacement project was delayed to the detriment of all stakeholders. In order to comprehend the contributing factors that contribute to the delays, the researcher's objective with this delay issue is to compare the fast track technique and not use it. The replacement project for the Situbondo Paramaan Bridge, which has fallen behind schedule, is the main subject of this study. The primary and secondary data for this study, which combines qualitative and quantitative research approaches, were processed using Microsoft Project 2016.The data were gathered straight from the project. With a focus on time management, the fast track technique is used to address project delay difficulties. This study aims to accelerate time so that the project can be finished on schedule or even earlier than the time agreed upon between the contractor and the project owner. The replacement project for the Paramaan Bridge in Kab. Situbondo has been delayed for a number of reasons. to t projects in order to avoid further promake it possible for these factors to be concentrated on completing the solution for subsequenject delays.